Measuring and communicating the effects of traffic incident management improvements. - Margiotta, Richard A.; Voorhies, Kenny; Lomas, Tim.; National Cooperative Highway Research Program; National Research Council (U.S.). Transportation Research Board (Washington, DC Transportation Research Board, 2004)
"This digest presents the results of NCHRP Project 20-7/Task 173, 'Measuring and communicating the effects of incident management improvements.' The research team (composed of Richard Margiotta and Kenny Voorhies ... and Tim Lomas ...) ..."
Caption title.
"May 2004."
Includes bibliographical references.
Available online.
Keywords: Traffic congestion -- Management; Express highways -- Management; Traffic accidents -- Management